Training interventions for healthcare providers offering group-based patient education. A scoping review. Issue 5 (May 2021) - Kristjansdottir, Olöf Birna; Vågan, André; Svavarsdóttir, Margrét Hrönn; Børve, Hilde Blindheim; Hvinden, Kari; Duprez, Veerle; Van Hecke, Ann; Heyn, Lena; Strømme, Hilde; Stenberg, Una
Highlights: Healthcare provider training in group patient education was examined in 27 studies. Reactions were mostly positive, with indications of positive effects on learning. Results on healthcare providers' skills and patient outcomes were inconclusive. Use of comparison groups, validated instruments and follow-up measures was rare. More attention is needed on theory, group facilitation and follow-up in trainings. Abstract: Objectives: To provide overview of research on training interventions for healthcare providers aimed at promoting competencies in delivering group-based patient education. Methods: A systematic literature search identified relevant studies. Data was extracted on training details, study design, outcomes and experiences. Results were summarized and qualitative data analyzed using content analysis. Results: Twenty-seven studies exploring various training interventions were included. Ten studies used qualitative methods, eight quantitative and nine mixed methods. Use of a comparison group, validated instruments and follow-up measures was rare. Healthcare providers' reactions to training were mostly positive. Several studies indicated positive short-term effects on self-efficacy and knowledge. Results on observed skills and patient outcomes were inconclusive. Results on healthcare providers' experience of delivery of group-based patient education following training were categorized into 1) Benefits of training interventions, 2) Barriers to implementation and 3) Delivery support. Conclusions: Further evaluation of training for healthcare providers delivering group-based patient education is needed before conclusions on training efficacy can be drawn. The results indicate an expanding research field still in maturation. Practice implications: Efficacy studies evaluating theoretically grounded training with clear attention on group facilitation and follow-up support are needed. Inclusion of validated instruments and long-term outcomes is encouraged.